Syrian National Identity The Stakes of the Essence and the Dialectic of Reason of State, Reason of Nation and Reason of World - Rahman, Houssam Abdel (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research is based on the Constructivist approach, which sees that the identity is socially-constructed rather than being determined and primordial, the research aims to demystify the transformations of the identity in Syria between the being of the authority of what is conceived on one hand, and the process of rebuilding the reality on the other, the transition from an "identity in itself" which has a subjective existence found with the founding the state-entity, reaching an "identity for itself" which its individuals are aware being affiliated to it. The awareness of this "identity for itself" is enhanced throughout two interlinked dynamisms, First: the domestic policies which participated in recognizing the National Personality through the crystallization of a mechanical social cluster in the sociological term of overlapping consensus over a national-political-economic community, and Second: the realpolitik based on the rational national interests, which by turn enhanced recognizing the difference with the friend and the enemy alike, and repositioned the conceivable authority about the national authority. These two dynamism coincided with the consolidation of the Westphalian system of nation-state in the Arab world. This research concludes that sub-national identities and transnational identities (pan-Arab, Kurdish, Islamic, pan-Syrian /Bilad al-Sham) are essential components of the Syrian national identity and are part of it, not the other way around. We are facing an overlap similar to chemical reactions, so that once the elements meet until they lose their first properties and then turn into a new compound that contains the properties of the constituent elements but does not coincide with any of them, this compound is nothing but the Syrian national identity, which in the end is only a "social constructed" . Hence, the continuous intervention to give one characteristic its supremacy over other characteristics, generates a conflictual reaction and an imbalance between the elements. ينطلق هذا البحث من مدخل المقاربة البنائية التي ترى أن الهوية بناء اجتماعي وليست معطى جوهري ونهائي، ويهدف إلى إزالة الغموض عن تحولات أنماط الهوية في سورية بين صيرورة سلطة المتخيّل وسيرورة إعادة بناء الواقع من "هوية بذاتها" لها وجود موضوعي وجدت مع إنشاء كيان الدولة إلى "هوية لذاتها" يعي أفرادها الانتماء إليها، ترسّخ الوعي بها عبر ديناميتين متشابكتين، أولاً، السياسات المحلية التي ساهمت بإدراك الذات الوطنية من خلال تبلور تكتل ميكانيكي مجتمعي بالمعنى السوسيولوجي تكوكب حول تفاهمات تداخلية سياسية-اقتصادية وطنية؛ ثانياً، السياسات الخارجية الواقعية المرتكزة على منطق المصالح العقلانية الوطنية التي عززت بدورها إدراك الاختلاف مع الآخر سواء الصديق أو العدو وأعادت تموضع سلطة المخيال حول الهوية الوطنية. هاتان الديناميتان تزامنتا مع ترسخ نظام الدولة-الأمة الويستفالي في الوطن العربي. يستخلص هذا البحث أن الهويات ما دون الوطنية والهويات العابرة للحدود (العربية، الكردية، الإسلامية، الشامية/بلاد الشام) هي مكونات أساسية للهوية الوطنية السورية وهي جزء منها وليس العكس. فنحن أمام تداخل أشبه بالتفاعلات الكيميائية، حيث ما أن تلتقي العناصر حتى تفقد خاصياتها الأولى ومن ثم تتحول لتشكل مركباً جديداً يحتوي خصائص العناصر المكونة ولكنه لا يتطابق مع أيٍّ منها، هذا المركب ليس إلا الهوية الوطنية السورية والتي ليست في نهاية المطاف إلا "بناء اجتماعي". ومن ثم فإن التدخل المستمر لإعادة إبراز خاصية وسيادتها على الخاصيات الأخرى، يولد تفاعلاً صراعياً واختلال في التوازن بين العناصر.